SG-APSIC1159: Control of hospital-acquired carbapenemase-producing carbapenem-resistant Enterobacteriaceae colonization: A descriptive study - Tuodi Wu; Li Jie; Maria Theresa Mapalo Muyot Cabahug; Philomena Liew; Chai Hairu; Suhailah Binte Nasir; Harminder Kaur; An Rongyan; Foo Shi Yun; Tan Seow Yen; Tan Thean Yen; Tan Si Huei (Cambridge University Press, 2023)
Objectives: Carbapenemase-producing carbapenem-resistant Enterobacteriaceae (CP-CRE) are nosocomial pathogens, and control of CP-CRE transmission is one of the most important infection control issues healthcare organizations face today. Increasing colonization acquisition and clinical infections of CP-CRE occurred in our institution in 2019. In this observational study, we monitored CP-CRE acquisition following implementation of multimodal control measures, and we describe the impact of this intervention on clinical infections. Methods: Increased hospital-acquired CP-CRE colonization and clinical infections were observed in early 2019. Increased CP-CRE surveillance was implemented to include CP-CRE contacts, patients with lengths of stay >7 days, patients with a recent history of hospitalization in other hospitals, and renal dialysis patients. The following interventions were also implemented: (1) isolation or placing CP-CRE patients in cohorts in a designated multidrug-resistant organism (MDRO) ward; (2) emphasis on hand hygiene and contact precautions; (3) mandatory use of gown and gloves for predefined 'high-risk' nursing activities, including diaper changing, toilet assistance, wound dressing, and handling urine or stool; (4) enhanced environmental and equipment cleaning; (5) regular audit and feedback regarding compliance; and (6) weekly feedback on ward-level CP-CRE acquisition. CP-CRE colonization cases and clinical infections were tracked by infection prevention and control nurses. Results: The hospital-acquired CP-CRE colonization rate was 4.39 per 10,000 patient days in 2019; it decreased slightly to 3.61 in 2020 and remained steady at 3.77 in 2021. The predominant CP-CRE genes were NDM, OXA-48-like, and KPC. There were 12 hospital-acquired CP-CRE infections in 2019, a rate of 0.37 per 10,000 patient days. This incidence decreased to 6 infections in 2020 and 3 infections in 2021, with corresponding infection rates of 0.19 and 0.09 per 10,000 patient days, respectively. Conclusions: Control of CP-CRE remains extremely challenging in hospitals with multibed open wards. A bundle approach to infection control showed a gradual reduction in CP-CRE cases, with a significant impact on the prevention of clinical infections.